Poly Royal 1937 (1937)
5th annual Poly Royal event. [00:00:11] A car pulls up to a house and two men run to get into the car, which speeds off [00:00:39] Another man is picked up [00:00:57] Men shovel sawdust or dirt out of a wagon and spread it on the ground in construction of an arena [00:02:08] Cows line up in front of a barn [00:02:31] A man talks into a microphone labeled "SoCo" [00:02:50] Panning shot of many cows and their owners [00:03:20] Pigs [00:03:50] Panning shot of cars in parking lot [00:04:40] Milking demonstration [00:05:32] A boy poses with his prize lamb [00:05:39] A tractor drives a course in the mud [00:05:58] Dark interior view of airplanes in a hangar [00:06:15] Horse riding demonstration [00:07:25] End of recording